The best practices in action using analogies to enhance background knowledge - D'Arcangelo, Marcia; Hoverman, Lynn; Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2006)
This program demonstrates the use of research-based instructional startegies. Specially see how using analogies in helps students learn to identify similarities and differences, stimulates students' higher-order thinking processes and leads students to see relationships between dissimilar pairs of elements and increase their understanding of new information
Additional teacher comments (5 min.) and support for using analogies in PDF files that accessible by computer
Title from title screen
Editors, Gerald Goldman, Ron Simon ; camera, Page McCarty ; sound, Derek St. Onge
Keywords: Learning; Analogy; Metaphor